Soft x-ray spectra of high temperature argon plasma for potential cell treatment - Poh, Hun Seng; Yap, Seong Ling; Teow, Sin Yeang; Tan, Han Yi; Yap, Seong Shan (Penerbit Universiti Kebangsaan Malaysia, 2023)
A plasma pinch is created when the current sheath collapses onto the axis in a plasma focus discharge. The plasma focus produces a high temperature and high density plasma, emitting soft x-ray with energy in the range of kiloelectronvolt. The soft x-ray is suitable for the radiography of biological samples, or as the source for microscopy or absorption spectroscopy of tissues which are not visible to conventional x-ray. Similar sources are available only from synchrotron radiation facilities with fairly low brightness. The argon plasma pinch produced by a plasma focus was investigated. The x-ray spectra was resolved with a set of filtered detector for the range of 1 to 20 Å. The plasma electron temperature measured was within 3 keV to 10 keV, with typical plasma density of 1019/cm3 . The discharge energy of 1.5 to 2.5 kJ at 1 mbar argon measured a peak current of 95 kA to 122 kA, and total soft x-ray energies of 22 to 52 J.